Prosedur tato kornea: sebuah laporan kasus - Tiara Alexander; Eunike Cahyaningsih (DiscoverSys Inc., 2021)
Background: Leukoma adherent is a condition where the formation of white cicatrix with iris incarceration involvement of the cornea. In addition to causing a decrease in visual acuity and blindness, leukoma adherent can also interfere with the appearance of the patient's eye. Corneal tattoo or keratopigmentation (KTP) is a procedure that disguises the color of the leukoma according to the color of the patient's eyes or irises. Corneal tattoo procedures can be performed superficially, intrastromal, or with a femtosecond laser. Corneal tattoo procedures can be carried out in various ways. It is necessary to study keratopigmentation thoroughly.Case: An 18-year-old male patient complained of white patches on his left eye, expanding for a year. The first spots appeared five years ago after being exposed to wood. On physical examination, visual acuity was 1/ in the left eye and 20/20 in the right eye. The patient underwent a corneal tattoo on the left eye using Vicryl 7.0 with Chinese ink.Conclusions: Corneal tattoo with intrastromal technique is one of the commonly used techniques. This procedure can use a suture needle or an angled knife to introduce the ink. The results of this procedure are quite satisfactory. However, the patient must still be educated on the possibility of further action for color fading or other complications that can harm the eyes. Latar belakang: Leukoma adherent merupakan kondisi terbentuknya sikatriks berwarna putih dengan keterlibatan inkarserasi iris pada kornea. Selain menyebabkan penurunan tajam penglihatan dan kebutaan, leukoma adherent juga dapat mengganggu penampilan mata pasien. Tattoo kornea atau kerato pigmentasi (KTP) merupakan prosedur yang menyamarkan warna leukoma sesuai dengan warna mata atau iris pasien. Prosedur tato kornea dapat dilakukan superfisial, intrastromal, ataupun dengan femtosecond laser. Prosedur tattoo kornea dapat dilaksanakan secara beragam, maka diperlukan studi yang membahas prosedur tattoo kornea secara menyeluruh.Kasus: Pasien laki-laki usia 18 tahun mengeluhkan bercak putih pada mata kiri yang semakin meluas sejak setahun. Bercak pertama kali timbul sejak 5 tahun lalu, setelah mata kiri terkena kayu. Pada pemeriksaan fisik didapatkan tajam penglihatan 1/ pada mata kiri dan 20/20 pada mata kanan. Pasien menjalani tindakan tattoo kornea pada mata kiri menggunakan vicryl 7.0 dengan tinta cina.Simpulan: Tattoo kornea dengan teknik intrastromal merupakan salah satu teknik yang umum digunakan. Prosedur ini dapat menggunakan suture needle ataupun angled knife untuk mengintroduksi tinta. Hasil dari prosedur ini cukup memuaskan namun pasien tetap harus diedukasi kemungkinan tindakan lanjutan atas peluruhan warna ataupun komplikasi lain yang dapat membahayakan mata.